Cephalic Vein Transposition versus Vein Grafts for Venous Outflow in Free-flap Breast Reconstruction - Edward I. Chang, MD; Regina M. Fearmonti, MD; David W. Chang, MD; Charles E. Butler, MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2014)
Introduction: When recipient veins for free-flap breast reconstruction are unavailable or inadequate, vein grafts or cephalic vein transposition (CVT) an option to provide alternate venous outflow. There are no comparative data to elucidate the indications and outcomes for each. We hypothesize that the CVT is as reliable as vein grafts when indicated. Methods: All consecutive cases where a CVT or venous vein grafts were used for free-flap breast reconstruction between 2000 and 2012 were reviewed. Patient demographics, operative notes, indications, and flap survival were compared between the 2 groups. Results: Ten patients underwent a CVT and 38 patients received a vein graft for insufficient venous outflow. There were no differences in average age, body mass index, or comorbid conditions between the groups. Similarly, there was no difference in previous radiotherapy, timing of reconstruction, or side of reconstruction. A CVT was used for salvage following venous thrombosis in 7 patients (70.0%) and for primary venous outflow in the remaining patients due to inability to use the internal mammary vein. Vein grafts were performed primarily in 31 patients, 22 for augmenting venous drainage (supercharge), 9 for the dominant venous outflow, and 7 for salvage of a thrombosis. One patient in each group suffered a complete loss of the free flap (cephalic: 10.0% vs vein graft: 14.3%, P = 0.36). Conclusions: The CVT is a reliable alternate venous outflow that can be used as a primary recipient vein or as a salvage option following venous thrombosis. Surgeons should consider a CVT when primary recipient veins are compromised or unavailable.